2011
DOI: 10.1002/ibd.21590
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between human intestinal dendritic cells, gut microbiota, and disease activity in Crohnʼs disease

Abstract: IL-6 production by intestinal DC is increased in CD and correlates with disease activity and CRP. Bacterially driven local IL-6 production by intestinal DC may overcome regulatory activity, resulting in unopposed effector function and tissue damage. Intestinal DC function may be influenced by the composition of the commensal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 72 publications
2
66
0
1
Order By: Relevance
“…Links between bacterial infections and autoimmune diseases of the gut have been found [98,99]. However, the complexity of the human microbiome may make it difficult to deconvolute the many cross-reactive peptides that could be driving this link.…”
Section:  Autoimmune Disease and The Gut Microbiomementioning
confidence: 99%
“…Links between bacterial infections and autoimmune diseases of the gut have been found [98,99]. However, the complexity of the human microbiome may make it difficult to deconvolute the many cross-reactive peptides that could be driving this link.…”
Section:  Autoimmune Disease and The Gut Microbiomementioning
confidence: 99%
“…115 It has recently been shown that IL-6 production by intestinal DCs is increased in CD and correlates with disease activity and C-reactive protein, and intestinal DC function may be influenced by the composition of the commensal microbiota. 116 Commensal microbiota, such as Bacteroides fragilis, express molecules such as polysaccharide A which protect against the proinflammatory effects of potentially pathogenic microbiota by stimulating IL-10-producing CD4þ T cells. [117][118][119] Similarly, the commensal Fecalibacterium prausnitzii has been shown to have antiinflammatory effects due to secreted metabolites which block NF-jB activation and IL-8 production.…”
Section: Microbiota Controls Host Immunity Effect On Intestinal Immunitymentioning
confidence: 99%
“…In general, studies have shown an increase in both DC and macrophage populations in the intestinal lamina propria in Crohn's Disease patients [20,32,33,[50][51][52]. Studies have also consistently shown that DCs in Crohn's Disease are more activated and have higher expression of microbial recognition receptors, particularly TLR4 [8,27,50,53,54]. These findings support intestinal phagocytes as likely key mediators of the pro-inflammatory response.…”
Section: Phagocyte Subsets In the Intestine Of Patients With Crohn's mentioning
confidence: 77%
“…However, it has been shown that IL-6 and IL-12 are over-produced by DCs from Crohn's Disease patients [53]. Consistent with this, Ng et al [54] showed that DCs from patients with Crohn's Disease express more IL-12p40 and IL6 compared to healthy controls. Finally, LPS stimulation of mucosal DCs in Crohn's Disease patients induced high secretion of TNFα and IL-8 [35].…”
Section: Phagocyte Subsets In the Intestine Of Patients With Crohn's mentioning
confidence: 79%